Time Course of Neuromuscular Adaptations to Knee Extensor Eccentric Training - Baroni, B. M.; Rodrigues, R.; Franke, R. A.; Geremia, J. M.; Rassier, D. E.; Vaz, M. A. (International Journal of Sports Medicine, 2013)
This study investigated the chronology of neural and morphological adaptations to knee extensor eccentric training and their contribution to strength gains in isometric, concentric and eccentric muscle actions. 20 male healthy subjects performed a 12-week eccentric training program on an isokinetic dynamometer, and neuromuscular evaluations of knee extensors were performed every 4 weeks. After 12 training weeks, significant increases were observed for: isometric (24%), concentric (15%) and eccentric (29%) torques; isometric (29%) and eccentric (33%) electromyographic activity; muscle thickness (10%) and anatomical cross-sectional area (19%). Eccentric and isometric torques increased progressively until the end of the program. Concentric torque and muscle mass parameters increased until the eighth training week, but did not change from this point to the twelfth training week. Eccentric and isometric activation increased at 4 and 8 training weeks, respectively, while no change was found in concentric activation. These results suggest that: 1) the relative increment in concentric strength was minor and does not relate to neural effects; 2) eccentric and isometric strength gains up to 8 training weeks are explained by the increased neural activation and muscle mass, whereas the increments in the last 4 training weeks seem to be associated with other mechanisms.
Keywords: resistance training; eccentric exercise; quadriceps femoris; isokinetic dynamometer; electromyography; ultrasonography